Analisis Pendidikan Karakter Perspektif Sayyid Muhammad dan Aplikasinya di Institusi Pendidikan Islam - Rofiqotul Masumah; Hawwin Huda Yana; Miftahur Rohman; Saryati Purwanigara (Bustanul Ulum Journal of Islamic Education, 2025)
Education is defined as a conscious and planned effort to actively develop students' self-potential, which includes physical, spiritual, intellectual aspects, personality, intelligence, and noble character. The purpose of this study is to explain the values of character education in the book At Tahliyah Wa At-Targhīb Fī At-Tarbiyah Wa At-Tahżīb. This research uses a literature method with a qualitative descriptive approach. The data was analyzed through content analysis to understand the concepts of character education in the book At Tahliyah Wa At-Targhīb Fī At-Tarbiyah Wa At-Tahżīb. The results of the discussion were that character education, described by Sayyid Muhammad in his book At Tahliyah Wa At-Targhīb Fī At-Tarbiyah Wa At-Tahżīb contains various aspects needed by the younger generation. Sulukul Insani as a concept of social interaction in society, the importance of awareness of social capital to others, and the active role of educational institutions are the keys to the successful implementation of character education.